How Does Career Calling Influence Preservice Teachers' Learning Engagement? A Multiple Mediating Roles of Occupational Self-Efficacy and Vocational Outcome Expectation - Shang, Weiwei; Yu, Tianzuo; Liang, Xianping; Wang, Ji; Su, Jiming (Frontiers in Psychology, 2022)
This study used social cognitive career theory (SCCT) to explore the relationships between career calling, occupational self-efficacy, vocational outcome expectation, and learning engagement among preservice teachers at a normal university in China. Data from 1,029 preservice teachers were analyzed using Structural Equation Modeling. The results revealed that career calling was found to be significantly and positively affected on learning engagement; occupational self-efficacy and vocational outcome expectation were identified as key mediators of this relationship. These findings advance our knowledge of how best to promote the learning engagement of preservice teachers and may inform the future design of teacher development programs.